Perawatan Komprehensif Rampan Karies pada Anak Usia Delapan Tahun - Triana N Yusuf; Jeffrey Jeffrey (Journal of Medicine and Health, 2020)
The prevalence of dental caries in Indonesia primary school is 60-80%. Dental caries is a continuous dynamic process involving repeating periods of demineralization by organic acids of microbial origin and subsequent remineralization by salivary components, but in which the overall environment is imbalanced towards demineralization. Rampant caries is a sign of gross dietary inadequacy, complete absence of oral hygiene practice or systemic illness. Rampant caries is suddenly appearing, widespread, rapidly burrowing type of caries, resulting in early involvement of the pulp and affecting those teeth usually regarded as immune to ordinary decay. This case report presents a case of rampant caries in an 8-year-old boy and the treatment. The cooperative behavior of patients and parents is needed for optimal results. Keywords: Rampant caries; caries in children; caries